REVIEW PAPER SIGNIFICANCE OF ENDOGENOUS AMINO ACID LOSSES IN THE NUTRITION OF SOME POULTRY SPECIES: A REVIEW - R. N. Soomro; J. Yao; M. E. Abd El-Hack; M. Asif Arain; I. H. R. Abbasi; M. Saeed; S. A. Soomro; M. A. E. Mohamed; R. Hu; Y. Qiao; X. Yang; M. Alagawany; et al. (Journal of Animal and Plant Sciences, 2018)
The accurate data on protein and amino acids digestibility of feed components is one of the ways to enhance nitrogen and protein utilization and to mitigate nitrogen pollution in a poultry farm. Digestibility and bioavailability of dietary nutrients depend on different factors like the type of feedstuffs, nutrients utilization, fiber contents, and diet adjustments in poultry. Diet formulation depends on dietary sources of protein, which is responsible to improve or maintain amino acid digestibility. The nutrients digestibility and absorption of the diet always decrease with increasing endogenous amino acid losses ( EAAL). A lot of factors such as age, species and breeds play important role in EAAL contents. Furthermore, the high values of EAAL have been recorded in early ages in comparison with advanced ages; this result may be owed to the incomplete development of the gastrointestinal tract (GIT) and low digestion in early age as reported by several researchers. The estimation method and factors of the environment are strongly effective on the accurate measurement of EAAL. The aim of this review article is to compare the results of from different methods and highlight the issue EAAL of various poultry species including broiler chickens, laying hens and turkey poults. Besides, this paper illustrates some comparative studies among the aforementioned species according to different ages and methods to correctly understand the nutritional values of feed components, nutrient digestibility and utilization. Based on the review of existing literature this paper direct the attention of researchers and poultry producers to improve the accuracy of estimating EAAL among various poultry models, and to improve the productive and reproductive performance on commercial basis. depending on the nutrient digestibility, requirements and
Keywords: endogenous amino acid losses; pollution; ammonia; age; poultry.